Electro-optic frequency shift of single photons from a quantum dot - Kapoor, Sanjay; Rodek, Aleksander; Mikołajczyk, Michał; Szuniewicz, Jerzy; Sośnicki, Filip Maksymilian; Kazimierczuk, Tomasz; Kossacki, Piotr; Karpiński, Michał (Nanophotonics)
Quantum dots (QDs) are a promising source of single photons mainly due to their on-demand operation. However, their emission wavelength depends on their size and immediate surroundings in the solid-state environment. By applying a serrodyne electro-optic phase modulation, we achieve a spectral shift up to 0.01 nm (3.5 GHz) while preserving the purity and indistinguishability of the photons. This method provides an efficient and scalable approach for tuning the emission wavelength of QDs without relying on nonlinear frequency mixing or probabilistic processes. Our results show that the electro-optic phase modulation enables stable and tunable spectral shifts, making it suitable for applications such as quantum communication, quantum key distribution, and primarily integrating remote quantum dot sources into large-scale quantum networks.

Aberration-optimized electro-optic time lens model using a tunable aperture - Kapoor, Sanjay; Sośnicki, Filip Maksymilian; Karpiński, Michał (APL Photonics)
Time lenses have been recognized as crucial components for manipulating ultrafast optical pulses in various applications, from ultrafast spectroscopy to the interfacing of optical quantum systems. A time lens is characterized by its chirp rate, which determines the focusing strength of the time lens, and accurate knowledge of this chirp is critical for precise dispersion compensation and minimizing aberrations. Here, we introduce a tunable time aperture model for sinusoidal time lenses that provides a more accurate estimate of the effective chirp rate without modifying the device. We derive a closed-form expression for the maximum phase error and show how it depends on the time aperture. We experimentally demonstrate a 1.6-fold improvement in spectral bandwidth compression of Gaussian pulses compared to the conventional approach. Our framework offers a practical tool for designing efficient temporal optical systems, benefiting applications in both classical and quantum optics where accurate spectro-temporal shaping is essential.

Frühe mathematische Bildung als Ausbildungsinhalt der Erzieherinnen- und Erzieher-Ausbildung stärken - Bruns, Julia; Gasteiger, Hedwig; Lastering, Bernd; Schopferer, Theresa; Zech, Detlev (25 Jahre Berufskolleg - Wegspuren und Zukunftspfade)

Advancing excited-state properties of two-dimensional materials using a dielectric-dependent hybrid functional - Ghosh, Arghya; Jana, Subrata; Hossain, Manoar; Rani, Dimple; Śmiga, Szymon; Samal, Prasanjit (Physical Review B)
Predicting accurate band gaps and optical properties of lower-dimensional materials, including two-dimensional van der Waals (vdW) materials and their heterostructures, remains a challenge within density functional theory (DFT) due to their unique screening compared to their bulk counterparts. Additionally, accurate treatment of the dielectric response is crucial for developing and applying screened-exchange dielectric-dependent range-separated hybrid functionals (SE-DD-RSH) for vdW materials. In this work, we introduce a SE-DD-RSH functional to the 2D vdW materials like <a:math xmlns:a="http://www.w3.org/1998/Math/MathML"><a:msub><a:mi>MoS</a:mi><a:mn>2</a:mn></a:msub></a:math>, <b:math xmlns:b="http://www.w3.org/1998/Math/MathML"><b:msub><b:mi>WS</b:mi><b:mn>2</b:mn></b:msub></b:math>, <c:math xmlns:c="http://www.w3.org/1998/Math/MathML"><c:mrow><c:mi>h</c:mi><c:mi>BN</c:mi></c:mrow></c:math>, black phosphorus (BP), and <d:math xmlns:d="http://www.w3.org/1998/Math/MathML"><d:mi>β</d:mi><d:mtext>−</d:mtext><d:mi>InSe</d:mi></d:math>. By accounting for in-plane and out-of-plane dielectric responses, our method achieves accuracy comparable to advanced many-body techniques like <e:math xmlns:e="http://www.w3.org/1998/Math/MathML"><e:mrow><e:msub><e:mi>G</e:mi><e:mn>0</e:mn></e:msub><e:msub><e:mi>W</e:mi><e:mn>0</e:mn></e:msub></e:mrow></e:math> and BSE@<f:math xmlns:f="http://www.w3.org/1998/Math/MathML"><f:mrow><f:msub><f:mi>G</f:mi><f:mn>0</f:mn></f:msub><f:msub><f:mi>W</f:mi><f:mn>0</f:mn></f:msub></f:mrow></f:math> at a lower computational cost. We demonstrate improved band gap predictions and optical absorption spectra for both bulk and layered structures, including some heterostructures like <g:math xmlns:g="http://www.w3.org/1998/Math/MathML"><g:msub><g:mi>MoS</g:mi><g:mn>2</g:mn></g:msub><g:mo>/</g:mo><g:msub><g:mi>WS</g:mi><g:mn>2</g:mn></g:msub></g:math>. This approach offers a practical and precise tool for exploring electronic and optical phenomena in 2D materials, paving the way for efficient computational studies of layered systems.

Words or Numbers? How Framing Uncertainties Affects Risk Assessment and Decision-Making - Bodenberger, Robin; Thommes, Kirsten
Senders of messages prefer to communicate uncertainty verbally (e.g., something is likely to happen) rather than numerically (such as 75%), leaving receivers with imprecise information. While it is well established that receivers translate verbal probabilities into numerical values that systematically deviate from the intended numerical meaning, it is less clear how this discrepancy influences subsequent behavioral actions. Thus, the role of verbal versus numerical communication of uncertainty warrants additional attention, to investigate two critical questions: 1) whether differences in decision-making under uncertainty arise between these communication forms, and 2) whether such differences persist even when verbal phrases are translated accurately into the intended numerical meaning. By implementing a laboratory experiment, we show that individuals place significantly lower values on uncertain options with medium to high likelihoods when uncertainty is communicated verbally rather than numerically. This effect may lead to less rational decisions under verbal communication, particularly at high likelihoods. Those results remain consistent even if individuals translate verbal uncertainty correctly into the intended numerical uncertainty, implying that a biased behavioral response is not only induced by miscommunication. Instead, ambiguity about the exact meaning of a verbal phrase interferes with decision-making even beyond potential mistranslations. These findings tie in with previous research on ambiguity aversion, which has predominantly operationalized ambiguity through numerical ranges rather than verbal phrases. Based on our findings we conclude that managers should communicate uncertainty numerically, as verbal communication can unintentionally influence the decision-making process of employees.

Foreign Language Use, Attribution Error, and Newcomer Integration - Thommes, Kirsten; Mehic, Miro

Soziale Medien als algorithmische Diskursmaschinen - Herzig, Bardo (SLLD (B). Spachlich literatisches Lernen und Deutschdidaktik)

Query Rewriting for Nested Navigational Queries over Property Graphs - Löhnert, Bianca; Augsten, Nikolaus; Okulmus, Cem; Ortiz, Magdalena (Proceedings of the 38th International Workshop on Description Logics (DL 2025), Opole, Poland, September 3-6, 2025.)

Ressourcenräume: Seerecht, Geopolitik und Wissenschaftsdiplomatie zwischen den Seychellen, Frankreich und der Bundesrepublik Deutschland um 1980 - Kunkel, Sönke; Sackel, Johanna (Räume in der Internationalen Geschichte)

Rechnen mit Beziehungen - operative Beziehungen erkennen, beschreiben und nutzen. Entwicklung einer digitalbasierten Lernumgebung mit der App Rechenfeld - Dettelbach, Andrea (Beiträge zum Mathematikunterricht 2025)

Normatives Modellieren im Kontext des Klimawandels – wie viel CO2 stoßen Lebensmittel aus? - Gildehaus, Lara; Liebendörfer, Michael; Hüsing, Sven; Gottschalk, Rebecca; Strauß, Franzisca (Realitätsbezüge im Mathematikunterricht)

Konstruktionistisches Geometrielernen durch epistemisches Programmieren in Scratch - Stoppel, Hannes; Hüsing, Sven (Beiträge zum Mathematikunterricht; 58)

Empowering Students to Gain Insights within Data Exploration Projects in the Classroom - Using, Modifying, and Creating Data Moves through a Scaffolded Use of Digital Tools - Hüsing, Sven; Podworny, Susanne (Symposium on integrating AI and data science into school education across disciplines)

Using SysML as a Modelling Language for Dataspaces - Kulkarni, Pranav Jayant; Zerbin, Julian; Koldewey, Christian; Bernijazov, Ruslan; Dumitrescu, Roman (2024 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))
Utilizing data is crucial for economic success, but a lack of interoperability and concerns about the misuse of ones own data are hindering the cross-organizational use of data. Dataspaces provide the infrastructure necessary to integrate heterogeneous data sources within an organization or ecosystem, enabling seamless data interaction and interoperability. In addition, data spaces strengthen data sovereignty through their decentralized nature, which enables organizations to effectively control and manage their data. However, challenges persist in managing the complexity and dynamic nature of dataspaces, requiring significant resources and technical expertise. The decentralized nature leads to a large and diverse number of stakeholders, who need to agree on the use and scope of a dataspace. Modeling is a common approach to cope with technical complexity and heterogeneous stakeholders. In this paper, we propose a version of SysML and a corresponding method that focus on the modelling of data spaces. We provide a dataspace modelling method to unify the understanding of dataspaces and scope among all stakeholders to simplify the design and development process.
Keywords: Dataspaces; Modelling; SysML; Gaia-X; System Specification

Igniting Knowledge Management for Assistance Systems in Maintenance: A Method for Knowledge Gathering - Skolik, Alexander Marcus; zur Heiden, Philipp; Donner, Johannes Aurelius Tamino; Priefer, Jennifer (ECIS 2025 Proceedings)

Geschlechterstereotype Selbstdarstellungen junger Frauen in der Ausbildungsvorbereitung - Schotten, Sarah Theresa; Otto, Franziska; Kremer, H.-Hugo (Jahrbuch der berufs- und wirtschaftspädagogischen Forschung 2025)

The Influence of Mathematical Achievement on the Development of Intuitive Probabilistic Reasoning in Lower Secondary School Students - Wiemann, Leon; Schroeder, Sascha; Halverscheid, Stefan (Proceedings of the 48th Conference of the International Group for the Psychology of Mathematics Eduction: Research Reports, Vol. 2)

Schmidt modes carrying orbital angular momentum generated by cascaded systems pumped with Laguerre–Gaussian beams - Scharwald, Dennis; Gehse, Lucas; Sharapova, Polina (APL Photonics)
Orbital angular momentum (OAM) modes are an important resource used in various branches of quantum science and technology due to their unique helical structure and countably infinite basis. Generating light that simultaneously carries high-order orbital angular momenta and exhibits quantum correlations is a challenging task. In this work, we present a theoretical approach to the generation of correlated Schmidt modes carrying OAM via parametric down-conversion (PDC) in cascaded nonlinear systems (nonlinear interferometers) pumped by Laguerre–Gaussian beams. We demonstrate how the number of generated modes and their population can be controlled by varying the pump parameters, the gain of the PDC process, and the distance between the crystals. We investigate the angular displacement measurement uncertainty of these interferometers and demonstrate that it can overcome the classical shot noise limit.

Die Konstruktion eines Fragebogens zur Messung der probabilistischen Intuition von Schüler*innen der Sekundarstufe I - Wiemann, Leon (Beiträge zum Mathematikunterricht 2025. 58. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Phononic crystallography of fibre-reinforced polymers using broadband acoustic waves - Wippermann, Mareen; Claes, Leander (2025 International Congress on Ultrasonics)